2004
DOI: 10.1074/jbc.m405083200
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Streptococcal Binding to Human Fibronectin Requires Specific Recognition of Sequential F1 Modules

Abstract: Fibronectin (Fn) binding by the Streptococcus pyogenes protein SfbI has been shown to trigger integrindependent internalization of this pathogen by human epithelial and endothelial cells. Here, using nuclear magnetic resonance spectroscopy and isothermal titration calorimetry in a dissection approach, the basis for the specificity and high affinity of the interaction between the N-terminal domain of Fn and SfbI is revealed. Each of the five Fn type 1 modules is directly involved in the interaction and is recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 46 publications
(64 reference statements)
4
76
0
Order By: Relevance
“…One possible explanation is the formation of a "fuzzy complex," or a dynamic ensemble of conformational states, upon binding NTD. This has been previously observed for other intrinsically disordered proteins, including the NTD-binding SfbI of S. pyogenes (39,40). Regardless of the origin of the peak disappearance, the NMR experiments indicate that NTD interacts specifically with the disordered region of LigBCen2 in the intact construct.…”
Section: Identification Of the Binding Sites Of Ntd On Ligbcen2-insupporting
confidence: 76%
See 2 more Smart Citations
“…One possible explanation is the formation of a "fuzzy complex," or a dynamic ensemble of conformational states, upon binding NTD. This has been previously observed for other intrinsically disordered proteins, including the NTD-binding SfbI of S. pyogenes (39,40). Regardless of the origin of the peak disappearance, the NMR experiments indicate that NTD interacts specifically with the disordered region of LigBCen2 in the intact construct.…”
Section: Identification Of the Binding Sites Of Ntd On Ligbcen2-insupporting
confidence: 76%
“…The ␤-strand-rich conformation formed by LigBCen2NR after binding NTD observed via far UV CD spectroscopy suggests that the binding of LigBCen2NR to NTD might be also mediated by a ␤-zipper interaction. However, the entropy-driven interaction of LigBCen2NR and NTD is distinct from the enthalpy-driven binding of other bacterial proteins known to bind NTD via the ␤-zipper interaction (Table 1) (23,39,46). In addition, we are unable to identify substantial sequence similarity between LigBCen2NR and BBK32 or other Fn-binding proteins, so additional study is needed to further characterize the binding between LigBCen2NR and NTD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…1B From the early characterization of Fn-binding proteins of S. aureus (3) to more recent studies (18), there is good evidence that the interaction with Fn is multivalent, i.e., between six and nine Fn molecules bind a single copy of FnBPA or FnBPB. We (19) and others (20) have suggested that multivalent binding of Fn to bacterial Fn-binding proteins is likely to play a role in invasion of human cells, and this hypothesis is supported by the observation that bacterial Fn-binding proteins from S. pyogenes also contain multiple Fn-binding sites (4,15). Multivalent binding is rather puzzling however, given the relative sizes of NTD (29-kDa) and FnBPA (40-kDa Fn-binding region).…”
Section: Resultsmentioning
confidence: 83%
“…The total surface area buried is Ϸ4,200 Å 2 . Although it seems clear, based on the relative K D s of FnBR/ 2-5 F1 and peptide/module interactions (4,15), that the full FnBPA-1/ 2-5 F1 and FnBPA-5/ 2-5 F1 interactions can largely be dissected in this way, we have only approximated the relative domain orientations of 3 F1 and 4 F1 in the intact complex. In addition, the FnBRs in the intact bacterial protein are likely to have less flexible N and C termini, which might influence their…”
Section: Resultsmentioning
confidence: 99%